The role of impulse purchase and brand orientation towards customer online purchase intention - Gunawan, Mochamad Chandra; Supardi,; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
Customer acceptance toward online purchase increased dramatically with a steady annual growth. More customers at all type of ages started to accept the online purchase as it is convenient and easy. The current majority of population plays important role as the strong supporter of digital implementation and development. The current generation were brought up with the internet and cellular phone. Thus their acceptance towards online transactions especially online shopping is being accepted without much questions. This study aims to evaluate the relationship between impulse buying and brand orientation towards purchase intentions. Both predictors are important as it may help the revenue generation of the service providers. Data were collected among 300 online customers from all type of ranges in order to obtain mass findings related to their feedback. Questionnaire was used for data collection and selection of respondent were based on convenient sampling. The results show that both impulse buying and brand orientation have a significant strong relationship towards purchase intention. Such result provides an information to the service provider that can helps them to design marketing and sales approach online. The result is useful for service provider’s promotions campaign and online purchase designs that may help them to rearrange the catalogue and process of buying for Indonesian market.